Effect of enzymatic hydrolysis on the physicochemical and emulsification properties of rice bran albumin and globulin fractions. (15th February 2022) - Wang, Junwen; Wang, Tengyu; Yu, Guoping; Li, Xiaoyi; Liu, Hengchen; Liu, Tong; Zhu, Jingshu
Abstract: In this study, albumin and globulin were separated from rice bran and hydrolyzed with trypsin. The fractions of these proteins and their hydrolysates were comparatively studied to understand the mechanisms of the functional changes. SDS–PAGE showed that the molecular weights of the two hydrolysates decreased. In addition, the number of α-helices and random coils of the two proteins increased, which was consistent with the structure observed by SEM. Oil-in-water emulsions were prepared from the hydrolysate of rice bran albumin and globulin, and their ability to resist environmental pressure (pH: 3–9; salt addition: 0–300 mM NaCl and thermal processing: 30–90 °C for 30 min) and stability were evaluated. In an acidic environment, the emulsion formed by globulin hydrolysate had a smaller particle size and higher absolute ζ-potential values. Due to electrostatic repulsion, the emulsions formed by the two hydrolysates were not stable under high salt conditions. Temperature had no significant effect on the ζ-potential of the emulsions formed by the two hydrolysates, although the particle size increased significantly when the temperature was higher than 50 °C. In contrast, the emulsion stabilized by globulin hydrolysate was more stable. Highlights: Hydrolysis could improve the functional properties and increase the flexibility of RBA and RBG. The emulsions stabilized by RBAH and RBGH had good thermal stability, but weak ionic stability. Compared with RBAH, RBGH had better storage stability.